The effect of ultrasonic treatments on cloudy quality-related quality parameters in apple juice - Ertugay, Mustafa Fatih; Baslar, Mehmet (ELSEVIER SCI LTD, 2014)
The effects of ultrasonic treatment on the cloudiness (cloud level and cloud stability), sedimentation and storage of apple juice were studied at various amplitude levels (50 and 100 mu m), pulse durations (50% and 100%), and temperatures (40, 50 and 60 degrees C). Ultrasound at high amplitude, temperature, and time minimized the coarse particles in the apple juice and increased its cloudiness quality. The ultrasonic treatment increased the cloudiness level up to 16.9 times and the cloud stability up to 9.8 times. Up to 58% of solid particles causing sedimentation were suspended after the treatment Even after storage for four months, the apple juice remained cloudy without any additional processing. Total yeasts and molds were completely inactivated (<1 log cfu/mL) by the ultrasonic treatment. These findings suggest that thermosonication could be considered a good alternative to conventional treatment in order to achieve the desired cloudiness in cloud apple juice processing. Industrial relevance: The article demonstrates some interesting results in using ultrasonic treatments on cloud quality parameters in apple juice. The ultrasonic treatments applied at high temperature improve dramatically cloud value and cloud stability, and decrease sedimentation level of the juice. The treatments also completely inactivate yeasts and molds in the juice. Thus thermosonication could be considered as a good alternative to achieve the desired cloudiness in apple juice processing. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Apple juice; Cloudiness; Sedimentation; Thermosonication; Ultrasound; POLYPHENOLIC COMPOUNDS; SONICATION; DISPERSIONS; DEGRADATION; PRESSURE; ORANGE; COLOR; Food Science & Technology